Pre-landslide topographic reconstruction in Baetis Chaos, mars using a CaSSIS Digital Elevation Model. (1st September 2022) - Guimpier, A.; Conway, S.J.; Pajola, M.; Lucchetti, A.; Simioni, E.; Re, C.; Noblet, A.; Mangold, N.; Thomas, N.; Cremonese, G.; ,
Abstract: Planview detailed morphological analysis of martian landslides is usually performed using orbital imagery such as from the ConTeXt camera (CTX) at 6 ​m/pix, the Colour and Stereo Surface Imaging System (CaSSIS) at 4.5 ​m/pix or the High-Resolution Imaging Science Experiment (HiRISE) at 0.25–0.5 ​m/pix. However, topographic information is key to fully understand a landslide's formation mechanism and its mobility, by estimating the material volumes mobilised and the spatial distribution of erosion and deposition. Digital Elevation Models (DEM) are required to carry out these analyses; nevertheless, there is currently a gap in landslide-volume studies between those using Mars Orbiter Laser Altimeter (MOLA) dataset at ∼450 ​m/pix or HRSC at 50–200 m/pix and those using HiRISE data at 1–2 m/pix, which is only partially filled by CTX elevation data at ∼20 ​m/pix. The CaSSIS camera on board the ESA/Trace Gas Obiter (TGO) can be used to produce DEMs, but so far, such data have not yet been used to conduct a landslide volume analysis. Here, we use three reconstruction methods (semi-automatic, morphology-based and tilted) on a CaSSIS DEM to estimate the initial topography and hence the volume and the distribution of erosion and deposition of a 6 ​km long landslide in Baetis Chaos. Despite the complex topography of the surrounding area due to the presence of an ejecta deposit beneath the landslide, we were able to estimate the landslide's volume and mass distribution. Using a tilted plane as part of estimating the initial topography produced the best results. We evaluated the success by considering the quantifiable balance between erosion and deposition (given the uncertainties) and more subjectively by considering whether the volume distribution matched with what was expected based on the morphology in images alone. Therefore, we recommend the use of this method for individual landslide studies in complex topography where detailed knowledge of the deposit-thickness distribution is required. The semi-automatic reconstruction method produces satisfactory volume estimates and would be better suited to studies where hundreds of landslides are present. We found that CaSSIS data can be used to successfully conduct such analyses, providing additional DEM coverage to study martian medium-scale landslides or other landforms of similar scale (5–15 ​km) with the notable benefit that it provides single-pass stereo image acquisition. Highlights: Digital Elevation Model are needed to estimates landslide's material volumes and distribution in order to fully understand their mobility. CaSSIS (Colour and Stereo Surface Imaging System) DEM have not yet been used to conduct such landslide analysis. Three reconstruction on a CaSSIS DEM have been used to estimate the volume and the material distribution of a landslide in Baetis Chaos on Mars. CaSSIS data can be used to conduct analysis and provide additional coverage to study medium-scale landslides or other landforms (scale 5–15 km).